Answer: -2x + 5x^2
Step-by-step explanation:
3x + 6x^2 - 5x - x^2 = x(3-5) + x^2(6-1) = -2x + 5x^2
Answer:
can you take a better picture?
Step-by-step explanation:
Answer: see below
Step-by-step explanation:
3x-12=7x+8 ⇔ given
-12=4x+8 ⇔ addition property of equality
-20=4x ⇔ subtraction property of equality
x=-5 ⇔ division property of equality
-----------------------
5(x-1)=4x+13 ⇔ given
5x-5=4x+13 ⇔ distributive property
x-5=13 ⇔ subtraction property of equality
x=18 ⇔ addition property of equality
Answer: $18.51
Step-by-step explanation:
She paid $50
Her total purchases
$9.99 + $21.50 = 31.49
Change = (50 - 31.49) = 18.51
#3.
in this case, all you need to do is to look at the intersecting point. each units represent 2, the coordinates of the intersection are (4,-1), so D is the choice.
#4. B is the choice. two lines either intersect once (one solution), never (parallel, no solution), or overwrap (merge, infinite solutions)